Komparasi Metode Inter-VLAN Routing : Studi Kasus Penggunaan SVI dan Router on a Stick berdasarkan simulasi pada Cisco Packet Tracer - Zaidan Fahrezi; I Ketut Sudaryana (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
Inter-VLAN Routing is an essential component in modern networks to enable communication between VLANs. Two popular methods for achieving this are Switch Virtual Interface (SVI) and Router on a Stick. This study aims to compare these two methods in terms of performance, efficiency, configuration complexity, and scalability. The research is conducted by designing a network scenario that represents a modern office environment and testing parameters such as throughput, latency, and resource utilization. The results of this study are expected to provide in-depth insights into the advantages and disadvantages of each method, helping network professionals choose the most appropriate method for their specific needs. This study also includes practical analysis of the implementation configuration on Cisco devices, with simulation-based testing and real-time performance measurements.